An Analysis of Teacher Talk in English Classroom Interaction of the Seventh Grade Students of SMPN 23 Oku - Nurul Afifah; Nopa Yusnilita; Vinna Riana Resiani (ETERNAL (English Teaching Journal), 2017)
The objectives of the research were to found out the kinds of teacher talk that used by English teacher during the classroom interaction and to know the students’ perception about teacher talk in classroom. The population of this research was 162 students of seventh grade students. The researcher only took 32 students as the sample by applying purposive sampling. The data were collected through observation and questionnaire. Then the researcher used descriptive method for analyzing the data. The result of this research showed that the teacher used all kinds of teacher talk while giving questions and feedback. In giving questions, teacher used procedural questions (23%), display questions (70%), and referential questions (7%). In giving feedbacks, the teacher used informing (38%), prompting (23%), encouragement (8%), criticizing (23%), ignoring (8%) as the feedbacks for incorrect answer. And for correct answer, the teacher used praising (75%) and summarizing (25%) in the class. For the students’ perception toward teacher talk used by the teacher while giving questions and feedbacks, the students agreed that teacher always use all of the feedback except ignoring. It concluded that the teacher talk which teacher used while giving questions and feedbacks in the English class of the seventh grade students at SMPN 23 OKU is good. In addition, English teachers in Junior High School were suggested to develop and improve their basic ability in managing their talk, especially the ability in giving the appropriate questions and good feedbacks to the students in English class. With all the type of their talk, the interaction between the teacher and the students will be built and increase. The teacher must be a good facilitator and motivator to the students in learning English.